2020
DOI: 10.3389/fcell.2020.607757
|View full text |Cite
|
Sign up to set email alerts
|

Tubeimoside I Inhibits Cell Proliferation and Induces a Partly Disrupted and Cytoprotective Autophagy Through Rapidly Hyperactivation of MEK1/2-ERK1/2 Cascade via Promoting PTP1B in Melanoma

Abstract: Tubeimoside I (TBMS1), also referred to as tubeimoside A, is a natural compound extracted from the plant Tu Bei Mu (Bolbostemma paniculatum), which is a traditional Chinese herb used to treat multiple diseases for more than 1,000 years. Studies in recent years reported its anti-tumor activity in several cancers. However, whether it is effective in melanoma remains unknown. In the current study, we discovered that TBMS1 treatment inhibited melanoma cell proliferation in vitro and tumorigenecity in vivo. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…TBMS-1 (20 and 40 μmol/L) effectively results in apoptosis of melanoma A375 cells by blocking the cell cycle in the G2/M phase, downregulating Bcl-2, and upregulating Bax (Rasul et al, 2012). Another study verified that TBMS-1 inhibits cell proliferations and results in toxic stress to cancer cells by promoting protein-tyrosinephosphatase1B (PTP1B) expressions in melanoma and activating the mitogen-activated protein kinase 1/2-extracellular signal-regulated kinase 1/2 (MEK1/2-ERK1/2) cascade pathway (Du et al, 2020). Small molecular drugs targeting the programmed cell death ligand 1 (PD-L1)/ programmed cell death protein 1 (PD-1) axis are effective for enhancing antitumor immunity.…”
Section: Melanomamentioning
confidence: 87%
“…TBMS-1 (20 and 40 μmol/L) effectively results in apoptosis of melanoma A375 cells by blocking the cell cycle in the G2/M phase, downregulating Bcl-2, and upregulating Bax (Rasul et al, 2012). Another study verified that TBMS-1 inhibits cell proliferations and results in toxic stress to cancer cells by promoting protein-tyrosinephosphatase1B (PTP1B) expressions in melanoma and activating the mitogen-activated protein kinase 1/2-extracellular signal-regulated kinase 1/2 (MEK1/2-ERK1/2) cascade pathway (Du et al, 2020). Small molecular drugs targeting the programmed cell death ligand 1 (PD-L1)/ programmed cell death protein 1 (PD-1) axis are effective for enhancing antitumor immunity.…”
Section: Melanomamentioning
confidence: 87%
“…Melanoma, a highly metastatic tumor, is the leading cause of death from skin cancer ( Tong and Young, 2014 ). Melanoma is largely fatal, though surgical resection of early-stage melanoma is frequently curative ( Sykes et al, 2016 ; Du et al, 2020 ). Therefore, the discovery of effective natural compounds against melanoma may have important public health implications.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it can play its role via AMPK signal pathway; on the other hand, it can also restrain lysosomal cathepsin to block autophagy flux, and act on colorectal cancer CRC cells ( Yan et al, 2019 ), cervical cancer cells ( Feng et al, 2018 ), and lung cancer cells ( Wang et al, 2020 ) according to these two ways. Besides, Du et al (2020) found that TBMS I could trigger the interruption of partial autophagy flux and cytoprotective autophagy in melanoma A375 cells, which was realized by over-activating MEK1/2-ERK1/2 cascade.…”
Section: Pharmacological Activitiesmentioning
confidence: 98%